Malignant Hepatic Solitary Fibrous Tumor - Kim, Hong Il; In, Seok Kyung; Yi, Hyung Suk; Lee, Min Jeong; Kim, Hyo Young (Journal of liver cancer, 2019)
Hepatic solitary fibrous tumors (SFTs) are mostly benign and rare because of information regarding the clinical symptoms, treatment, and prognosis of their malignant forms is currently lacking. A literature review concerning malignant SFTs revealed that there were a few cases where patients experienced abdominal right upper quadrant (RUQ) pain as their first clinical symptom, and metastases were found after being diagnosed with hepatic SFT. Here, we report a patient who was previously healthy without any clinical symptoms such as RUQ pain or weight loss, but had the appearance of a metastatic mass as the first clinical presentation before a primary hepatic SFT was detected (J Liver Cancer 2019;19:143-148)